Guanidinium chloride–18-crown-6 (2/1) - Wei, Bin (International Union of Crystallography, 2012)
In the crystal of the title compound, 2CH(6)N(3) (+)·2Cl(−)·C(12)H(24)O(6), the 18-crown-6 molecule is located across an inversion center. The guanidinium cation links to the 18-crown-6 molecule and chloride anion via N—H⋯O and N—H⋯Cl hydrogen bonds.